Vernal keratoconjunctivitis: state of art and update on treatment - Brindisi, Giulia; Cinicola, Bianca; Anania, Caterina; De Castro, Giovanna; Nebbioso, Marcella; Miraglia del Giudice, Michele; Licari, Amelia; Caffarelli, Carlo; De Filippo, Maria; Cardinale, Fabio; Duse, Marzia; Zicari, Anna Maria (Acta Biomedica Atenei Parmensis, 2021)
Vernal keratocongiuntivitis (VKC) is a chronic inflammatory disease affecting the ocular conjunctiva and cornea. It is a rare and underestimated pathology, whose missed or delayed diagnosis can lead to the development of serious ocular complications. Moreover, despite VKC symptoms are well known, they can overlap and be mistaken with allergic conjunctivitis. In fact, diagnostic criteria and severity grading are not standardized yet. The pathogenesis of VKC is still controversial and it is difficult to identify a single mechanism underlying the chronic ocular inflammation. Different studies hypothesized both allergies and autoimmune diseases and also oxidative stress contribute significantly to the origin of the disease. However, the unclear pathogenesis and the lack of specific disease biomarkers make treatment a challenge. The standard therapy includes antihistamines, anti-inflammatory and immunosuppressant drugs and novel therapies are currently under investigation. However, considering treatment guidelines and recommendations are not well defined yet, therapy should be personalized on the clinical features of the patient. This paper provides an overview of the VKC and updates on the challenges that need to be addressed in the future to improve the management of the patient with this disease and improve his quality of life.